Control of the Mexican bean weevil Zabrotes subfasciatus with vegetable oils, trashing residues, inert materials and malathion - Barbosa, Flávia Rabelo; Yokoyama, Massaru; Pereira, Pedro Antônio Arraes; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; p margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The effects of malathion 500 CE, neem (Azadirachta indica A. Juss.) and soybean (Glycine max Merrill) oils, inert materials and trashing residues on the control of Zabrotes subfasciatus (Coleoptera:Bruchidae) were evaluated on bean seeds (Phaseolus vulgaris L.), using the cultivar Carioca and two lines containing the protein arcelin (Arc1 and Arc3). The experiment was carried in a laboratory at Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão, Santo Antônio de Goiás, GO, Brazil, under noncontrolled conditions. The highest levels of protection against Z. subfasciatus were observed in Arc1, with reduction in the number of eggs, number of emerged adults and percentage of damaged seeds than in Arc3 and Carioca cultivar. The number of eggs, number of emerged adults and the percentage of damaged seeds were reduced when the seeds were treated with malathion, neem and soybean oils. There was not difference in percentage of damaged seeds between malathion and neem oil. The treatment of the seeds using ant hill ground showed low efficiency, and trashing residues and dolomitic lime did not show reduction on the progeny and damage of Z. subfasciatus.